Assessing genetic structuring for endangered "Chelonia mydas" (Testudines: Cheloniidae) in southwest Cuba using microsatellites - Luis Javier Madrigal-Roca; Julia Azanza-Ricardo; Georgina Espinosa-López; Ken Oyama; F. Alberto Abreu-Grobois; Omar Chassin-Noria (Revista de Investigaciones Marinas, 2023)
Understanding the population genetic structure of the species is essential for determining the possible management units (UM) and their conservation and/or sustainable exploitation with it. Chelonia mydas is recognized as an endangered philopatric turtle. This work aims to describe the population structure of the green turtle in southwestern Cuba through traditional analytical approaches and allocation methods. The collections were made between 1998 and 2007 on five beaches in the Cuban southwest. Seven microsatellite loci from 149 individuals were amplified and genetic variability parameters were calculated. The population structure was inferred through the use of Wright's F, Analysis of Molecular Variance (AMOVA), and population assignment algorithms based on Bayesian analysis (STRUCTURE) and factorization of sparse non-negative matrices (implemented in R). Most of the loci were not in Hardy-Weinberg equilibrium, and several presented linkage disequilibrium. The AMOVA and differentiation statistics suggest the presence of structure at the geographical level analyzed. The highest value of ΔK and the lowest value of cross-entropy were reached for K = 2, a result that suggests that in southwestern Cuba there is the contribution of two ancestral populations of Chelonia mydas. Relative migration estimates indicate active genetic exchange between nesting colonies in southwestern Cuba.